The impact of artificial intelligence use on students’ autonomous writing (Journal of Applied Learning and Teaching, 2025)
This research investigates the impact of Artificial Intelligence (AI) tools on students’ independent writing skills, specifically in preparing for the IELTS test in Iran, in light of the growing reliance on artificial intelligence in education. This study employs a mixed-methods research design, supplementing quantitative data from a 29-item Likert-scale questionnaire targeting 103 students with qualitative data from semi-structured interviews with 23 students and 11 teachers. The results indicate that, although artificial intelligence tools contribute largely to the organization, creativity, and self-confidence of the students’ writing, most still depend on the teachers for the content. The students have demonstrated increased motivation and versatility in their thinking, with artificial intelligence serving as both an enhancement of their writing skills and a potential threat in the form of unfair criticism or over-reliance. Clearly, teachers can effectively and ethically integrate artificial intelligence into writing instruction to maximize its benefits and minimize its drawbacks. This, in turn, enhances the understanding and appreciation of the potential applications of artificial intelligence in education.